Hyperbolic Expressions in One Direction’s Love Song Lyrics - Ruminda Ruminda; Nida Kharimah (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2017)
Hyperbole is an exaggerate expression which is often used in literary works such as poem, novel and song lyric. This research will analyze how the hyperbolic expressions are shown in One Direction’s love song lyrics by using Claridge’s theory of hyperbole. The objects taken for this research are from love song lyrics of One Direction which are taken from 3 albums. The finding shows that from the analyzed data, the hyperbolic expressions are shown from their gradability and intensification, context, and problem of literal meaning.